Assessment of the Business Prospects of Bankrupt Debtors in the Implementation of the Going Concern Principle: A Legal Review Under Indonesia’s Bankruptcy Regime - Albert Hasea Samuel Sihombing; Aurora Jillena Meliala (Eduvest - Journal of Universal Studies, 2026)
This research examines the assessment of business prospects of bankrupt debtors in implementing the going concern principle under Indonesian Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payments (KPKPU). A significant gap exists between the normative objectives of going concern and its practical application in Indonesia's commercial court system. Indonesian bankruptcy regulations lack detailed technical mechanisms for prospectivity assessment, leading to ad hoc and subjective decision-making. Despite recognizing going concern as fundamental, success rates reach only 30-40% of filed cases, signaling systematic failures. This study uses a juridical-empirical approach with prescriptive-analytical methods, blending normative legal analysis and empirical data from curators, supervisory judges, and creditors. Comparative analysis with bankruptcy regimes in the United States, United Kingdom, Germany, and France identifies five key parameters: (1) liquidity and cash flow adequacy, (2) asset quality and marketability, (3) revenue generation capacity and market positioning, (4) management capability and turnaround experience, and (5) independent auditor opinion on going concern status. The research recommends a hybrid model integrating England's Company Voluntary Arrangement (CVA) (flexible, cost-effective), France's short observation periods (4-6 months with automatic stay), and simple litmus test-based assessment suited to Indonesian court capacity and MSME-dominated economy. This addresses unique challenges while ensuring creditor protection and efficiency. The framework boosts business rescue effectiveness and supports evidence-based bankruptcy reforms, especially amid Law 37/2004 revisions in the 2026 National Legislative Program (Prolegnas).